Antioxidant and Antiaging Potential of Salak Fruit Extract (Salacca zalacca (Gaert.)Voss) - Widowati, Wahyu; Dani, Dani; Vera, Vera; Yuninda, Viranda Andria (Majalah Obat Tradisional, 2023)
Natural skin aging is indicated by a loss of skin structure and integrity caused by external factors including UV exposure. This exposure causes oxidative stress on skin cells, initiates aging, and degradation of extracellular matrix (ECM) structure which is composed of many proteins, including collagen and elastin. ECM degradation is caused by the increased activity of proteolytic enzymes, one of which is elastase (closely related to wrinkling). To inhibit oxidative stress during the photoaging process, the skin needs antioxidant compounds. Salak (Salacca zalacca (Gaert.)Voss) is a fruit that is rich in antioxidants because it contains flavonoid, phenolic, and polyphenolic compounds, including chlorogenic acid. The purpose of this study is to demonstrate the antioxidant activity and antiaging properties of salak fruit extract (SFE) as a candidate for active ingredients in the prevention of aging. To determine the antioxidant activity of SFE, 2,2-diphenyl-1-picrylhydrazil (DPPH) scavenging and ferric reducing antioxidant power (FRAP) assays were performed, while elastase assays were performed to determine the anti-aging properties of SFE. The IC50 values for DPPH scavenging and FRAP activity of SFE were 107.52 μg/mL and 16.82 μg/mL with the highest activity at 68.79% and 97.96%, at concentrations of 200 and 50 μg/mL, respectively. Meanwhile, the anti-aging properties determined through the elastase assay showed an IC50 value of 19.71 μg/mL with the highest inhibition 72.50% at a concentration of 66.67 μg/mL. SFE has the potential as an active ingredient in preventing aging through its antioxidant activity and anti-aging properties.